VD_FINDINFO Jug / 2022 / 432 vom 4. Mai 2022 - VD Tribunal cantonal (2022)
INJURE, MENACEDROIT PÉNAL, CONTRAINTEDROIT PÉNAL, DOMMAGES À LA PROPRIÉTÉDROIT PÉNAL, PARTIE CIVILE | 144 al. 1 CP, 144 al. 3 CP, 177 al. 2 CP, 180 al. 1 CP, 181 CP, 10 al. 3 CPP (CH), 126 CPP (CH), 147 al. 3 CPP (CH)